2016
DOI: 10.1007/s13139-016-0444-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Molecular Subtypes of Invasive Ductal Carcinoma of Breast with Glucose Metabolism in FDG PET/CT: Based on the Recommendations of the St. Gallen Consensus Meeting 2013

Abstract: Purpose This study aimed to investigate the relationship between the SUVmax of primary breast cancer lesions and the molecular subtypes based on the recommendations of the St. Gallen consensus meeting 2013. Methods Clinical records of patients who underwent F-18 FDG PET/CT for initial staging of invasive ductal carcinoma (IDC) of the breast were reviewed. A total of 183 patients were included. SUVmax was correlated with the molecular subtypes defined by the St. Gallen Consensus Meeting 2013, i.e., luminal A-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…For 18 F-FDG, the luminal A and luminal B (HER2 negative) subtypes had relatively low uptake, while the HER2 positive and triple negative subtypes had relatively high uptake. Our result was consistent with some previous studies. ,,,,,,, Perhaps, positive ER/PR and negative HER2 contribute to low 18 F-FDG uptake, while negative ER/PR and positive HER2 contribute to high 18 F-FDG uptake. The molecular mechanisms have not yet been elucidated clearly with regard to this speculation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For 18 F-FDG, the luminal A and luminal B (HER2 negative) subtypes had relatively low uptake, while the HER2 positive and triple negative subtypes had relatively high uptake. Our result was consistent with some previous studies. ,,,,,,, Perhaps, positive ER/PR and negative HER2 contribute to low 18 F-FDG uptake, while negative ER/PR and positive HER2 contribute to high 18 F-FDG uptake. The molecular mechanisms have not yet been elucidated clearly with regard to this speculation.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, higher 18 F-FDG uptake is significantly associated with ER negativity and PR negativity. Also, higher 18 F-FDG uptake is in the HER2 overexpressing subtype and triple negative subtype, while lower 18 F-FDG uptake is in the luminal A subtype. However, the exact threshold was not given in most studies because of the wide-overlapping 18 F-FDG uptake values among various subtypes. Even if some cut-off values for identifying molecular subtypes were present in a few studies, there were vast differences among them.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] St. Gallen International Expert Consensus also has great benefits for treatment-related decision in patients with cancer. 24 Our study confirmed these advantages for treatment-related decision in patients with early-stage invasive breast cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, PET/ CT is clinically indicated only for stage III breast cancer patients and so stage I and II breast cancers, which represent the majority, have been excluded from the analysis of these retrospective datasets. Radiogenomic analyses to date have principally focused on metabolic activity parameters of the primary tumor, most commonly via analysis of the maximum standardized uptake values, but also via analysis of the metabolic tumor volume and total lesion glycolysis (30)(31)(32)(33)(34)(35)(36)(37)(38)(39). While more advanced metrics such as histogram-based features have only recently been explored (30).…”
Section: Fdg Pet/ctmentioning
confidence: 99%